PRODUCTION OF MOZZARELLA CHEESE FROM BUFFALOâS MILK USING DIRECT ACIDIFICATION TECHNIQUE - Sta Cruz, Joy Christine V.; Ocampo, Lerma C.; Abella, Mina P. (Proceeding Buffalo International Conference, 2013)
Buffalo milk was processed to identify the effect of directly adding an acidulant namely,Â citric acid and lactic acid.Â Â Low-moisture mozzarella cheese was produced from buffalo milkÂ by direct acidification technique using either 10% citric acid (Treatment 1) or 10% lactic acid (Treatment 2). The effect on the percentage mozzarella yield, degree of meltabilityÂ , stretchability, color and chewiness were determined. Microbial analysis was also performed using Â psychrotrophic plate count method.The results of the study revealed that theÂ Â mozzarella cheese yield was 20.18%Â Â for Treatment 1 andÂ Â 20.6% for Treatment 2 and did not differ (studentâs T test P<0.05).Â Â As for the functionalÂ properties, mozzarella cheese in treatment 1 had aÂ Â meltability score of 110.67 mm and aÂ Â stretchability score of 146 cm when compared with mozzarella cheese in treatment 2 that registered aÂ Â meltability scoreÂ Â of 59.17 mm and a stretchability scoreÂ Â of 89.75 cm.On the basis of the sensory evaluation, the results indicated that the degree of chewiness, and stretchability of mozzarella cheese in treatments 1 and 2 did not differ with commercially available mozzarella (P<0.05).Â Â However,Â the meltability and colorÂ of mozzarella cheese in Treatment 2 differed significantly with commercially available mozzarella (P<0.05). Pyschrotrophic plate counts obtained were found to be within theÂ acceptable range for processed mozzarella and the product can beÂ kept for one month at frozen storage condition.We therefore conclude that the direct acidification technique using 10% citric acid will yield a consumer-acceptable mozzarella cheese product made from buffalo milk.